THE ROLE OF THE COURTS IN THE PUBLIC POLICY DOMAIN IN SOUTH AFRICA - Mogale Malapane; Nyane, Hoolo (Obiter, 2023)
During the pre-democratic constitutional dispensation, South African public law was marked by the pre-eminence of the executive and the legislature in a parliamentary system of government. The courts were generally loath to review matters related to policy. The adoption of the interim and subsequently the final constitutions changed the position by making the Constitution of the Republic of South Africa, 1996 the supreme law of the country, with separation of powers between the three branches of government. The approach of the courts has changed noticeably from restraint to activism. Their role in reviewing policies has been steadily growing. They are now thrust into the formulation of government or public policy, which traditionally fell within the ambit of the executive branch of government. This new-found role of the courts has led to concerns that the judiciary’s constant interference in the policy domain borders on violating the hallowed principle of separation of powers. The central argument of this article is that the courts’ intervention in the public policy domain, if not handled with caution, has the potential to undermine the principle of separation of powers implicit in the South African Constitution.